Screening and impurity removal device to improve the accuracy of moisture content detection device for rice - Tang, Han; Xu, Changsu; Zhao, Jiale; Wang, Yijia (International Journal of Agricultural and Biological Engineering, 2022)
An online detection device that used the capacitance method to detect the moisture content of rice in a combine harvester was designed and found a low detection accuracy because of the high impurity content of the samples. To solve this problem, a screening and impurity removal device was designed in this study, and the structural parameter range of the screw conveyor was the focus of the design. To determine the best structural parameters and operating parameters of the device, models of rice grains and short stems were established by the discrete element method. The Discrete Element Method (DEM) simulation test was carried out according to the Box-Behnken response surface method. When the rotating speed was 300 r/min, the diameter of spiral blade was 146 mm, the pitch was 80 mm, the diameter of rotating shaft was 30.6 mm, and the minimum impurity content was 0.27%. The density distributions and movement characteristics of the rice grains and short stems in the optimized screening and impurity removal device were studied. An experiment was carried out to compare data for the moisture content of rice measured by the online moisture content detection device before and after the installation of the screening and impurity removal device and the results of the 105°C drying method. The results showed that the impurity content of rice ranged from 0.26% to 0.37%, and the maximum effective screening rate was 90.99% after screening. The screening and impurity removal device significantly reduced the error in the moisture content measured by the online detection device, the error range was 0.12%-2.55%. This study provides a method for accurate online detection of moisture content and provides a reference for the design and simulation of related screening devices.Keywords: combine harvester, parameter optimization, rice, motion characteristics, discrete element modelDOI: 10.25165/j.ijabe.20221506.7299Citation: Tang H, Xu C S, Zhao J L, Wang Y J. Screening and impurity removal device to improve the accuracy of moisture content detection device for rice. Int J Agric & Biol Eng, 2022; 15(6): 113–123.